Analisis Kasus Perikatan: Wanprestasi dalam Putusan Pengadilan Negeri Jakarta Barat Nomor 785/PDT.G/2023/PN.JKT.BRT - Putra, Akasyah Rizwan Kurnia; Karo, Erland Zuhdi Karo; Hisyam, Cyrill Milanesta (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Wanprestasi is the debtor's negligence in fulfilling promised performance as defined in Articles 1234 and 1238 of the Civil Code, including failure to perform what was promised, performing inappropriately, being late, or violating the prohibitions of the agreement. This research uses a normative juridical method with a case study approach based on the West Jakarta District Court Decision Number 785/Pdt.G/2023/PN Jkt.Brt to analyze the multipurpose financing agreement case.The case chronology begins with Multipurpose Financing Agreement Number 70413741911 dated September 6, 2019, between PT Clipan Finance Indonesia Tbk (Plaintiff) and Suryani (Defendant) for the purchase of a BMW 320i worth Rp 1,009,620,000 with installments of Rp 16,827,000 per month for 60 months, secured by fiduciary. The Defendant stopped paying after the 20th installment on May 6, 2021. The Plaintiff sent warning letters on May 14 and 22, 2021. The vehicle became evidence of a pyramid scheme crime according to Supreme Court Decision Number 583 K/KPid.Sus/2022. The Plaintiff sued for breach of contract with a demand of more than IDR 1.5 billion plus IDR 500 million in immaterial damages, confiscation, and execution of fiduciary duties. The trial was cancelled because the Defendant failed to appear despite being legally summoned; the judge acknowledged the agreement as valid by considering Articles 1320 and 1338 of the Civil Code, and the breach of contract was proven from Exhibits P-1 to P-19. However, the lawsuit was not ontvankelijk verklaard because the calculation of material losses (0.4%/day fine, penalties, etc.) had no clear legal basis.